Customer Management: Creating a Sense-Making Framework for Developing Economies - Ritz, Mary (British Journal of Marketing Studies, 2016)
The aim of the study was to gain an understanding of why most organizations fail in the effective management of the customer despite the fact that it is well accepted and understood that the customer is an integral part of the business and the reason business exists. Although various strategies have been implemented such as, customer service, customer experience, and customer relationship management, the phenomenon remains a challenge. Many reasons could be attributed to the failure of implementing customer management strategies, including a lack of a holistic approach, insufficient buy-in first from leadership and followed by employees, short-term focus instead of long-term, and budget constraints. Though customer management frameworks that advocate for a customer centric approach exist, which is holistic in nature and incorporate a systems’ thinking perspective, the frameworks tend to take a western viewpoint or a developed economy paradigm. The assumption seems to be that the frameworks will work and be effective anywhere without being context specific. Subsequently, the study aimed to establish if the customer management phenomenon should not be context specific for it to yield better results. As a progression from this base, the ultimate objective of the research was to create a customer management framework for a specific context, i.e. a developing economy. The Research Methodology assumed was qualitative, and Grounded Theory was the general methodology applied for generating new theory. Data collection methods adopted were: documents, one-on-one in-depth interviews, and an online questionnaire. The sample and population were individuals from a developing economic (Africa), specifically South Africa and Zimbabwe. The research findings established that there are some general customer management principles that are similar and hold true across different socio-economic environments; however, the level of understanding and execution of these principles is fundamentally different. It can be concluded that a customer centric model specifically for a developing world is appropriate to a degree since market conditions and political, social, and economic conditions are different. Recommendations of the study include creating a sense-making customer management framework for a developing economy that is based on a systems thinking paradigm and that takes into consideration external factors such as politics, social, and the economic environment. The framework must be easy to understand and not require huge financial resources or investment to implement and sustain because the developing world (generally) tends to lack capital.